The conjuring - Hayes, Chad; Hayes, Carey W.; DeRosa-Grund, Tony; Safran, Peter, 1965-; Wan, James, 1977-; Wilson, Patrick, 1973-; Farmiga, Vera; Livingston, Ron; Cowan, Rob (Producer); Taylor, Lili; New Line Cinema Corporation; Safran Company; et al. (Burbank, CA : Warner Home Video, 2013)
Before there was Amityville, there was Harrisville. Based on the true life story, it tells the tale of how world renowned paranormal investigators Ed and Lorraine Warren were called upon to help a family terrorized by a dark presence in a secluded farmhouse. Forced to confront a powerful demonic entity, the Warrens find themselves caught in the most horrifying case of their lives.
Originally released as a motion picture in 2013.
Special features: scaring the "@$*%" Out of You.
Director of photography, John R. Leonetti ; music, Joseph Bishara ; editor, Kirk Morri.
Ron Livingston, Vera Farmiga, Lili Taylor, Patrick Wilson.
Rated: R for sequences of disturbing violence and terror.
DVD, NTSC, region 1, widescreen presentation, dual layer; Dolby Digital 5.1.
Keywords: Warren, Ed -- Drama; Warren, Lorraine -- Drama; Parapsychology -- Drama; Haunted houses -- Drama; Horror films; Thrillers (Motion pictures); Feature films; Video recordings for the hearing impaired